Financial Expertise of the Board, Risk Taking, and Performance: Evidence from Bank Holding Companies - Minton, Bernadette A.; Taillard, Jérôme P.; Williamson, Rohan (Journal of Financial and Quantitative Analysis, 2014)
Abstract Financial expertise among independent directors of U.S. banks is positively associated with balance-sheet and market-based measures of risk in the run-up to the 2007–2008 financial crisis. While financial expertise is weakly associated with better performance before the crisis, it is strongly related to lower performance during the crisis. Overall, the results are consistent with independent directors with financial expertise supporting increased risk taking prior to the crisis. Despite being consistent with shareholder value maximization ex ante, these actions become detrimental during the crisis. These results are not driven by powerful chief executive officers who select independent financial experts to rubber stamp strategies that satisfy their risk appetite.